Fracture Resistance of K3 Nickel-Titanium Files Made from Different Thermal Treatments. (14th November 2016) - Choi, JinWook; Oh, Soram; Kim, Yu-Chan; Jee, Kwang-Koo; Kum, KeeYeon; Chang, SeokWoo
Abstract : The purpose of this study was to compare fracture resistances of K3 nickel-titanium files made from different thermal treatments. K3 (SybronEndo, Orange, CA), K3XF (SybronEndo), and experimentally heat treated K3 (K3H) were used. For the cyclic fatigue test, the samples were rotated with up-and-down motion in the artificial canal with the curvature of 60 degrees until the fracture occurred. The number of cycles to fracture (NCF) was measured. For the torsional fracture test, the samples were tightly bound and rotated until the fracture occurred. Elastic modulus (EM), ultimate torsional strength (UTS), and angle of rotation to fracture (ARF) were measured. The results were statistically analyzed by one-way ANOVA. The NCF of K3H was higher than those of K3 and K3XF (P < 0.05 ). The EM of K3XF and K3H was lower than that of K3 (P < 0.05 ). There was no significant difference in UTS. The ARF of K3XF was higher than that of K3 (P < 0.05 ). K3XF and K3H showed more flexibility than K3. The maximum torsional angle of K3XF was higher than that of K3, but there was no significant difference on the UTS in all three groups.